Investigating the moderating role of resilience on perceived stress and psychological well-being of retail employees during the COVID-19 pandemic - Naidoo, Rebecca Tiffany; Hoque , Muhammad (Orapuh Journal, 2025)
IntroductionThe COVID-19 pandemic significantly altered traditional work arrangements, accelerating the adoption of remote work across various sectors. This transition posed new psychological challenges for employees, particularly in terms of perceived stress and well-being. Resilience may play a moderating role in buffering the negative effects of stress in such contexts.PurposeThis study examined the moderating role of resilience in the relationship between perceived stress and psychological well-being among retail employees working under remote conditions during the COVID-19 pandemic.MethodsA cross-sectional survey was conducted among head office associates of a South African retail organisation (Company X). Out of 1,500 surveys distributed electronically, 158 were completed. Standardised instruments—the Perceived Stress Scale (PSS-10), Psychological Well-Being Scale (PWB), Brief Resilience Scale (BRS), and a modified Survey of Perceived Organisational Support (SPOS)—were used to collect data. Analysis was performed using IBM SPSS Version 27, including the PROCESS macro to test for moderation effects.ResultsFindings revealed a significant negative relationship between perceived stress and psychological well-being (β = -1.13, p = .01). Resilience significantly moderated this relationship (interaction β = -0.04, p = .02), indicating that individuals with higher resilience experienced better psychological well-being despite high levels of perceived stress.ConclusionResilience plays a crucial role in mitigating the adverse psychological effects of perceived stress in remote work environments. Organisations should prioritise resilience-building interventions and supportive structures to enhance employee well-being and adaptability during and beyond crisis situations.